DIVERSITY OF THE ORDER HYMENOPTERA IN RICE PLANTATION IN MANEMBO-NEMBO DISTRICT AS AN ECOLOGICAL INDICATOR - Gulbudin Hikmatiar Idris; Christny Ferdina Evie Rompas; Utari Satiman; Johanna Zusye Wantania (Universitas Negeri Manado, 2023)
This research aims to determine habitat conditions as an ecological indicator and measure the level of diversity of insects of the order Hymenoptera on rice plantations in the Manembo-nembo sub-district. The method used in this research is quantitative descriptive. Insect samples were collected using the sweeping net and yellow pan trap methods. The Shannon-Wiener diversity index formula, Pielou's similarity index (E), and Simpson dominance index (C) are used to measure the level of diversity. The results of research on rice plantations found insects of the Hymenoptera order as many as 35 genera, 16 subfamilies and 14 families with a total of 470 individuals with normal habitat conditions where Hymenoptera insects can still carry out activities on rice plantations. Wasp insects from 24 genera also have functions as biological control agents, most of which are parasitoid and predatory wasps, which have potential as ecological indicators in rice plantations in the Manembo-nembo sub-district. The level of diversity is included in the medium criteria, as is the evenness index value. In contrast, the dominance index is included in the low criteria even though the Pimplinae family dominates rice cultivation in the Manembo-nembo sub-district.